Characteristics of overpressure and thermal effects of methane–air explosions in tunnels - Linlin Gu; Zhenjing Nie; Yi Li; Zhen Wang; Chuyuan Huang; Xianfeng Chen (Fuel, 2026)

Nonlinear abiotic transformation of a representative organic micropollutant in a deep stratified reservoir: Critical roles of iron and dissolved organic matter - Linlin Wang; Yi Li; Longfei Wang; Li Lin (Water Research, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

Clinical and Molecular Characterization of Five Additional Individuals With SATB2-Associated Syndrome in Guangxi - Sheng Yi; Qinle Zhang; Fei Chen; Xunzhao Zhou; Qiang Zhang; Shang Yi; Xiaofei Zhang; Jiale Qian; Linlin Wang; Shujie Zhang; Biyan Chen; Zailong Qin; et al. (Biochemical Genetics, 2026)

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

Unlocking circularity in rural waste management in northwest China: A systematic framework to quantify energy-environment-pollution nexus - Yuansheng Huang; Linlin Wang; Yi Liu; Yihan Chen; Xinglin Zhang; Yiliang He (Journal of Cleaner Production, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Tailoring monoglyceride oleogel crystallization by eutectic and crystal nucleation disturbance: functional frozen specialty fat for use in croissants - Yanxia An; Yi Han; Ziwei Liu; Jingyuan Su; Jian Zhang; Keke Liu; Linlin Li (Food Research International, 2026)

Oleogels in flour-based foods: an overview from the perspective of crystalline structure and functional performance - Yi Han; Linlin Li; Lukai Ma; Jingyuan Su; Yang Zhao; Jian Zhang; Yanxia An (Food Chemistry, 2026)

Seasonal-spatial distribution and prevailing wind analysis of Martian dust devils in Amazonis Planitia using a multi-scale attention network - Linlin Shi; Gan Liu; Jialong Lai; Xu Ma; Feifei Cui; Xiaoping Zhang; Yi Xu; Qiquan Yang (Science China Earth Sciences, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

Bisphenol S and Neurological Health: An Integrated Overview of Neurotoxicity and Underlying Mechanisms - Xing Zhang; Linlin Wu; Dingqi Hua; Bin Zhang; Xi Wang; Linchang Li; Yi Wang; Jiangbo Zhu (Molecular Neurobiology, 2026)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

Impacts of output-based ETS and subsidies on CCS retrofitting in China’s coal-fired power plants - Changsheng Yi; Linlin Xu; Yaling Tian (International Journal of Greenhouse Gas Control, 2025)

Constructing artificial interphase layer of polyoxovanadates with high oxidizability and reversibility to boost dendrite-free lithium metal anode - Yihai Song; Jiayuan Zhang; Chunhui Zhang; Linlin Fan; Jian Song; Yundong Cao; Yi Feng; Hong Liu; Guanggang Gao (Chemical Engineering Journal, 2025)

Hesperidin-loaded self-assembled supramolecular hydrogel based on quaternized chitosan as efficient photothermal antibacterial dressing for MRSA-infected wound healing - Yamin Xiong; Yi Hao; Linlin Ding; Jinjin Li; Yuan Cao; Shuhui Fan; Fangxia Guan; Leiliang He (Carbohydrate Polymers, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Lacticaseibacillus paracasei SB27 enhances its gastrointestinal tolerance, adhesion and colonization by producing biofilm - Yinxue Liu; Linlin Hao; Yisuo Liu; Lu Jiang; Huaxi Yi (Food Bioscience, 2025)

Response patterns and community assembly processes of gut microbiota in grass carp subjected to various protein sources and their implications for growth and metabolism - Minglang Cai; Linlin Yang; Lei Zhong; Shouqi Xie; Yi Hu (Fish Physiology and Biochemistry, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

RBM15 Knockdown Impairs the Malignancy of Cervical Cancer by Mediating m6A Modification of Decorin - Huimin Wang; Chun Li; Qiong Wei; Enjing Zhang; Yi Yang; Linlin Sha; Dan Wang (Biochemical Genetics, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

Feasibility evaluation of cottonseed protein concentrate to replace soybean meal in the diet of juvenile grass carp (Ctenopharyngodon idellus): Growth performance, antioxidant capacity, intestinal health and microflora composition - Linlin Yang; Minglang Cai; Lei Zhong; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

Evaluation of soybean meal replacement by Clostridium autoethanogenum protein in diets for juvenile grass carp (Ctenopharyngodon idellus) - Linlin Yang; Minglang Cai; Shouqi Xie; Yi Hu; Junzhi Zhang (Aquaculture, 2024)

From tissue lesions to neurotoxicity: The devastating effects of small-sized nanoplastics on red drum Sciaenops ocellatus - Zhicheng Sun; Xin Peng; Linlin Zhao; Yi Yang; Yugui Zhu; Linlong Wang; Bin Kang (Science of The Total Environment, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

Co-seismic ionospheric disturbances characteristics in different azimuths following the 2022 Mexico earthquake from GNSS observations - Linlin Li; Shuanggen Jin; Yi Chai (GPS Solutions, 2024)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Analysis of mRNA and MicroRNA Expression Profiles of Nervous Tissues and Reproductive Tissues in Male Procambarus clarkii After Silencing IAG - Rong Sun; Shaokui Yi; Linlin Shi; Kianann Tan; Ruixue Shi; Siqi Yang; Yanhe Li (Marine Biotechnology, 2023)

PM2.5-bound metals and blood metals are associated with pulmonary function and Th17/Treg imbalance: A panel study of asthmatic adults - Nannan Liu; Dan Wang; Jiayu Tian; Xin Wang; Hao Shi; Caihong Wang; Yi Jiang; Min Pang; Xiaozhou Fan; Jing Zhao; Liangpo Liu; Hongyan Wu; et al. (Chemosphere, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Construction of CoTiO3/TiO2/Ti composite catalytic membrane for degradation of tetracycline via peroxymonosulfate activation: Reactive oxygen species and electron transfer pathways - Yi Li; Linlin Wang; Longfei Wang; Weijie Wu; Fangjie Zhang; Haijiao Xie (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

Application of interim PET-CT in first-line treatment decision-making for lymphoma - Linlin Huang; Yi Zhao; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2023)

Targeted preparation of biochar for the application as composting additive: Influence mechanism of feedstock properties on biochar derived from traditional Chinese herb residue - Haoyu Tang; Aijun Li; Linlin Yi; Yongda Huang; Qian Deng; Yangwei Wu; Hong Yao (Process Safety and Environmental Protection, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Seasonal distribution of the early life stages of the small yellow croaker ( Larimichthys polyactis ) and its dynamic controls adjacent to the Changjiang River Estuary - Min Xu; Yihe Wang; Zunlei Liu; Yong Liu; Yi Zhang; Linlin Yang; Fei Wang; Hui Wu; Jiahua Cheng (Fisheries Oceanography, 2023)
The distribution of the early life stages of Larimichthys polyactis indicates the availability of suitable spawning and nursing grounds and enables a better understanding of the distribution of its geographic subpopulations and isolation. Large‐scale quantitative ichthyoplankton surveys of L. polyactis were performed from March to July 2018, and a numerical hydrodynamic model was applied to explore the spatiotemporal distribution and habitats of L. polyactis early life stages adjacent to the Changjiang River Estuary. Two distinct early life stage distribution patterns were found. One occurred during March and April in the deep waters seaward of the Changjiang River bottom plume front, to the east and southeast of the Changjiang River Estuary. The other occurred in May and June throughout the entire water column in coastal waters to the east and north of the Changjiang River Estuary. Rising seasonal temperatures, and the local dynamic processes such as the Changjiang River plume, determined the transitions between the two distribution patterns. A potential fish larval migration route from the southern deep shelf waters to the northern coastal waters within the motor‐trawl prohibition line was suggested. This study contributes to our understanding of the mixture of habitats used by the two L. polyactis subpopulations in the southern Yellow Sea and the East China Sea.

Insight into the design and construction of Cr substituted Co-based columnar activated coke catalysts for effective and reliable removal of methylbenzene and Hg0 concurrently - Lei Gao; Lei Yi; Dong Xie; Hanqing Wang; Caiting Li; Linlin Li; Yijin Liu; Jinke Xie; Yihui Zhou; Yingyun Liu (Fuel, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Estimating small structural motions from multi-view video measurement - Enjian Cai; Yi Zhang; Xiaodong Ji; Xinzheng Lu; Linlin Xie; Yuncheng Zhuang; Taisen Zhao; Guangwei Lin (Engineering Structures, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Alteration of alpha and beta diversity in nekton community by extreme marine heatwave events: An example from the East China Sea - Zunlei Liu; Linlin Yang; Liping Yan; Hui Zhang; Yi Zhang; Min Xu; Yan Jin; Jiahua Cheng (Frontiers in Marine Science, 2022)
In the year of 2016 to 2017, record-breaking marine heatwave (MHW) events occurred along the Chinese coast, exerting severe impacts on coastal fishes and fisheries. However, the response of the nekton community to MHW events still remains poorly understanding. Thus, to investigate the influences of the MHW events on species composition dynamics, this study conducted a survey on nekton communities in the northern East China Sea in the summers during 2014 to 2017. The recently-developed “heatwaveR” package was adopted to describe the variation characteristics of heatwaves within the study area, based on high-resolution remote-sensing sea surface temperature products. We also compared variations in the community structures of different biological groups before (2014–2015) and during the occurrence of the MHW events (2016–2017). During the MHW events, temperature increased by approximately 2.3°C in both 2016 and 2017. Compared with those before the MHW events, the biomass and dominance of several important crustaceans decreased, and the biomass of warm water affinity species increased significantly, while their richness and diversity decreased; the biomass of warm temperature affinity species declined significantly, while their diversity increased slightly. These results show the difference in the response rates of species with different thermal preferences and different species compositions to the extreme climate change. Beta diversity analysis revealed that the inter-group variation before and during the MHW event exceeded the intra-group variation, proving that MHWs changed the community structure to a certain extent. PERMANOVA test showed that the species compositions of planktivorous fish (FG1) and small-omnivorous fish (FG2) in the feeding-functional groups were significantly different before and during the MHW event, which may be attributed to the impact of MHWs on oligotrophic fishes through thermal preference and the trophic cascade effect. There was no significant change in the species compositions of other functional groups, indicating that medium-trophic and eutrophic fishes possessed certain adaptability to MHWs. Regarding fisheries management under extreme warming events, it would be advisable to diagnose temperature anomalies in the early stage, monitor changes in species abundance in the early life cycle, and then rapidly develop suitable fishing strategies.

High levels of serum IL-10 indicate disease progression, extramedullary involvement, and poor prognosis in multiple myeloma - Xiaoyan Yue; Linlin Huang; Yang Yang; Yi Zhao; Donghua He; Xiaoyan Han; Gaofeng Zheng; Yi Li; Enfan Zhang; Zhen Cai; Xin Huang; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2022)

Incorporating egg-transporting pathways into conservation plans of spawning areas: An example of small yellow croaker (Larimichthys polyactis) in the East China Sea zone - Zunlei Liu; Yan Jin; Linlin Yang; Liping Yan; Yi Zhang; Min Xu; Jianhua Tang; Yongdong Zhou; Fen Hu; Jiahua Cheng (Frontiers in Marine Science, 2022)
Backward-in-time Lagrangian model can identify potential spawning areas by reconstructing egg drift trajectories, contributing to accurately designing potential priority conservation plans for spawning areas. In this study, we apply this approach to investigate the small yellow croaker ( Larimichthys polyactis ) with commercial value in China. A two-step spatial random forest (RF) model is used to predict the occurrence probability and abundance of their eggs and describe the optimal ecological range of environmental factors. A priority protection index (BPPI) of the spawning areas is established by combining the sites with the optimal occurrence and abundance and integrating backward tracking pathways. The result indicates that the model with 1-2 day time lags of environmental variables shows the optimum explanatory power. Temperature and salinity are the most important factors affecting oogenesis and show a regime shift in the response curve. They reflect the physiological regulation of parental sexual maturation by the environment. In addition, egg abundance correlates more strongly with chlorophyll-a (Chl a) concentration and depth, suggesting that parents prefer environments with shallow water and high prey density for spawning activities. The egg retrieval shows that the potential spawning sources are distributed near the southeastern part of the oogenesis site, with a maximum egg dispersal distance of no more than 30 km. This finding confirms that the coastal regions of Jiangsu Province are an important spawning ground for the small yellow croaker, making a significant contribution to the productivity and resilience of the fish.

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Identifying Priority Conservation Areas of Largehead Hairtail (Trichiurus japonicus) Nursery Grounds in the East China Sea - Zunlei Liu; Yan Jin; Liping Yan; Yi Zhang; Hui Zhang; Chuyi Shen; Linlin Yang; Jiahua Cheng (Frontiers in Marine Science, 2022)
Identifying the spatio-temporal distribution hotspots of fishes and allocating priority conservation areas could facilitate the spatial planning and efficient management. As a flagship commercial fishery species, Largehead hairtail ( Trichiurus japonicus ) has been over-exploited since the early 2000s. Therefore, the spatio-temporal management of largehead hairtail nursery grounds could effective help its recovery. This study aims to predict juvenile largehead hairtail distribution patterns and identify priority conservation areas for nursery grounds. A two-stage hierarchical Bayesian spatio-temporal model was applied on independent scientific survey data (Catch per unit effort, CPUE) and geographic/physical variables (Depth, Distance to the coast, Sea bottom temperature, Dissolved oxygen concentration and Net primary production) to analyze the probability of occurrence and abundance distribution of juvenile largehead hairtail. We assessed the importance of each variable for explaining the occurrence and abundance. Using persistence index, we measured the robustness of hotspots and identified persistent hotspots for priority conservation areas. Selected models showed good predictive capacity on occurrence probability (AUC = 0.81) and abundance distribution ( r = 0.89) of juvenile largehead hairtail. Dissolved oxygen, net primary production, and sea bottom temperature significantly affected the probability of occurrence, while distance to the coast also affected the abundance distribution. Three stable nursery grounds were identified in Zhejiang inshore waters, the largest one was located on the east margin of the East China Sea hairtail national aquatic germplasm resources conservation zones (TCZ), suggesting that the core area of nursery grounds occurs outside the protected areas. Therefore, recognition of these sites and their associated geographic/oceanic attributes provides clear targets for optimizing largehead hairtail conservation efforts in the East China Sea. We suggested that the eastern and southern areas of TCZ should be included in conservation planning for an effective management within a network of marine protected areas.

Correction to: Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC‑7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC-7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Development of genome-wide SNPs for population genetics of Collichthys lucidus - Linlin Zhao; Meijie Jiang; Fangyuan Qu; Dan Yi; Shouqiang Wang; Zhaohui Zhang (Conservation Genetics Resources, 2018)

Genome survey sequencing of red swamp crayfish Procambarus clarkii - Linlin Shi; Shaokui Yi; Yanhe Li (Molecular Biology Reports, 2018)

Staphylococcus enterotoxin profile of China isolates and the superantigenicity of some novel enterotoxins - Menglu Shen; Yi Li; Linlin Zhang; Songbao Dai; Jiashun Wang; Yongqing Li; Lei Zhang; Jinhai Huang (Archives of Microbiology, 2017)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Construction and de novo characterization of a transcriptome of Chrysanthemum lavandulifolium: analysis of gene expression patterns in floral bud emergence - Yi Wang; He Huang; Yueping Ma; Jianxin Fu; Linlin Wang; Silan Dai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

The expression of analgesic-antitumor peptide (AGAP) from Chinese Buthus martensii Karsch in transgenic tobacco and tomato - Linlin Lai; Tingting Huang; Yi Wang; Yanfeng Liu; Jinghai Zhang; Yongbo Song (Molecular Biology Reports, 2009)